Clinical, Histopathological and Molecular detection of cutaneous papillomatosis associated with bovine papillomavirus types 1and 2 in cattle from Al-Qadissiyia Province - Khalefa Ali Mansour (Kufa Journal for Veterinary Medical Sciences, 2016)
This study was designed to evaluate the clinical, histopathological and molecular features of cattle warts disease in Al-Qadissiyia goverment. Fourteen samples from skin lesions were collected from cattle that were diagnosed as cutaneous papilloma by clinical examination. All samples were examined for the presence of cutaneous fibropapillomatosis and confirmed histopathologically and  by molecular detection by (PCR) for BPV-1 and BPV-2 as causative agents for the bovine cutaneous papillomatosis.. The results of this study showed that lesions were mostly located on the head and neck, perineal region, under the chin and around eyes. The histopathological changes of cauliflower-like growths of varying size (1-4 cm3) revealed various degrees of hyperplasia,  hyperkeratosis and acanthosis in all samples .The results of multiplex PCR for genotyping (BPV-1 and BPV-2) by using specific primers for L-major capsid protein revealed that eleven out of fourteen tissue samples were positive results for (BPV-1-L1 gene) and all the samples were negative result   for  (BPV-2-L2 gene) . On conclusion the bovine papillomatosis Who was diagnosed in Al-Qadissiyia Province is caused by bovine papillomavirus types 1 (BPV-1-L1 gene)  and has atypical characteristic clinical singes which make it easily to distinguish from other skin disease .